Analisis Kesalahan Berbahasa Teks Anekdot Kelas X MAN 1 Tasikmalaya dalam Kategori Linguistik - Ai Cahyani; Wita Adia Amelia; Alif Rizki Kurohman; Ai Siti Nurjamilah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the language errors contained in the text of the anecdote by class X MAN 1 Tasikmalaya students in the category of phonology, morphology, syntax, semantic, and spelling. The approach used in this study is a qualitative approach with a descriptive method of analysis. Research is conducted through several stages, i.e. (1) data collection, (2) data description, (3) data analysis, and (4) yield. Data collection techniques used include observation, interviews, and library studies. Research data is taken from the anecdote text made by students, then analyzed to identify the form of errors in language. The results of the study show that there are errors in various linguistic aspects, including phonology errors in the form of pronunciation and letter writing, morphology errors in the formation of words, syntactic errors in the preparation of sentences, as well as semantic errors that cause meaning to be ambiguous or inappropriate. In addition, there was also an error in the use of spelling, such as a mistake in writing punctuation and capital letters. Based on the results, this study is expected to contribute in learning Indonesian, especially in improving students' abilities in writing texts that match the language rules.